The Use of Natural Learning Media to Increase Early Childhood Motivation in Learning - Hasanah, Ainul; Firdausiyah, Raudlatul; Aliyah, Siti; Khatimah, Sri Idaman; Ulfah, Ulfah (GENIUS: Indonesian Journal of Early Childhood Education, 2023)
This study aims to determine the use of natural media materials on early childhood learning motivation. The indicators of learning motivation observed were full of enthusiasm, self-confidence, and high concentration power. This study used observation, interview, and documentation methods with data analysis techniques, the Miles and Huberman models. The results showed that the use of natural materials such as turmeric, cherry leaves, rice, pebbles, and banana stems as media in early childhood learning can motivate children to carry out learning activities.   Abstrak Penelitian ini bertujuan untuk mengetahui penggunaan media bahan alam terhadap motivasi belajar anak usia dini. Indikator motivasi belajar yang diamati adalah penuh semangat, rasa percaya diri, dan daya konsentrasi yang tinggi. Penelitian ini menggunakan metode observasi, wawancara, dan dokumentasi dengan teknik analisis data  model Miles dan Huberman. Hasil penelitian menunjukkan bahwa penggunaan bahan-bahan alami seperti kunyit, daun kersen, beras, batu kerikil, dan pelepah pisang sebagai media dalam pembelajaran anak usia dini dapat membuat anak termotivasi untuk melakukan aktivitas belajar.